2022
DOI: 10.4081/ejtm.2022.10449
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors related to anxiety of children and adolescents before elective surgery

Abstract: The goal of this study was to evelaute the preoperative anxiety in children and adolescents and to identify some of the risk factors associated with the incidence of anxiety in 9–18 years old group. Children and adolescents 9–18 years old hospitalized the night before elective surgeries were analyzed in terms of incidence and severity of anxiety using the State-Trait Anxiety Inventory (STAI) measure. Of the 164 patients, 111 (67.6%) suffered from preoperative anxiety. The incidence of anxiety in children aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Notably, even though the older age group spanned up to 12 years of age, most children in that age group were at the lower end of the range. Risk factors for higher anxiety in children include a history of hospitalization or surgery 5 . We did not notice any difference in anxiety/fear or behavior in children with previous anesthesia, but we did not assess the history of other health care interventions.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Notably, even though the older age group spanned up to 12 years of age, most children in that age group were at the lower end of the range. Risk factors for higher anxiety in children include a history of hospitalization or surgery 5 . We did not notice any difference in anxiety/fear or behavior in children with previous anesthesia, but we did not assess the history of other health care interventions.…”
Section: Discussionmentioning
confidence: 86%
“…Risk factors for higher anxiety in children include a history of hospitalization or surgery. 5 We did not notice any difference in anxiety/fear or behavior in children with previous anesthesia, but we did not assess the history of other health care interventions.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Age is believed to be negatively correlated with preoperative anxiety, which means that anxiety is higher in younger patients and decreases with increasing age. Ahmadipour et al [ 34 ] reported that the incidence of anxiety in children 9–12 years of age was approximately three times higher than those 12–18 years of age. The findings of a study by Cui et al support this observation: preschool children were more anxious than school-age children [ 35 ].…”
Section: Discussionmentioning
confidence: 99%